Benchmarking the first generation of production quality Arm‐based supercomputers. (11th November 2019) - McIntosh‐Smith, Simon; Price, James; Poenaru, Andrei; Deakin, Tom
Abstract: In this paper, we present scaling results from two production quality supercomputers that use the first generation of Arm‐based CPUs that have been optimized for scientific workloads. Both systems use Marvell ThunderX2 CPUs, which deliver high core counts and class‐leading memory bandwidth. The first system is Isambard, a Cray XC50 "Scout" system operated by the GW4 Alliance and the UK Met Office as a Tier‐2 national HPC service. The second system is one of three Arm‐based HPE Apollo 70 systems delivered as part of the Catalyst UK project, running at the University of Bristol. We compare scaling results from these two systems with three Cray XC50 systems based on Intel Skylake and Broadwell CPUs. We focus on a range of applications and mini‐apps that are important to the UK national HPC service, ARCHER, and to our project partners. We also compare the performance and maturity of the state‐of‐the‐art toolchains available on Arm‐based HPC systems.